2019
DOI: 10.1111/apps.12198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Personality Traits and Moral Values on Employee Well‐Being, Resilience and Performance: A Cross‐National Study

Abstract: Research examining the relationship at the interface of personality, values, moral foundations and its impact on employees’ subjective well‐being, resilience, job performance and satisfaction is almost non‐existent. This study addresses this Special Issue’s call focusing on the key antecedents and consequences of resilience on individual and/or organisational level outcomes. It does so by analysing data from two different, though comparative cross‐national studies in Australia and India. Employing a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 98 publications
(167 reference statements)
2
46
0
1
Order By: Relevance
“…Human resilience conceptions point to indicators of a person's adaptation to life, which perforce encompasses their work. Therefore conceptions of resilience have been extended to teachers based on the idea that resilience as an individual's trait or attribute may be manifest in teachers who remain in the profession because it is claimed that resilience is vital in dealing with the demands of complex organisations (Athota et al 2019) such as schools (see also Chap. 2).…”
Section: Teachers' Resiliencementioning
confidence: 99%
“…Human resilience conceptions point to indicators of a person's adaptation to life, which perforce encompasses their work. Therefore conceptions of resilience have been extended to teachers based on the idea that resilience as an individual's trait or attribute may be manifest in teachers who remain in the profession because it is claimed that resilience is vital in dealing with the demands of complex organisations (Athota et al 2019) such as schools (see also Chap. 2).…”
Section: Teachers' Resiliencementioning
confidence: 99%
“…Employees are considered important assets of organizations; for this reason, there has been a recent increase in interest in their subjective well-being, due to serious problems such as rethinking goals, social adjustment, psychological capacity, and employee happiness. Incidentally, it has been identified that ethical leadership characteristics can predict the dimensions of SWB [15]. Subjective well-being suggests frequent pleasant emotions, infrequent unpleasant emotions, and life satisfaction, where these three factors are are combination of cognitive and affective components.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, hurting other people is likely to affect well-being of the perpetra-tor in a negative direction, which makes the self-processes described above even more relevant when considering such type of immoral behavior. The same applies to at least two of the Big Five personality traits (McCrae, Costa, 2003), as these basic tendencies to think, feel and act have proved to be correlated with the values preferred by the person (Athota, Budhwar, Malik, 2019). Agreeableness, by definition strongly associated with empathy (McCrae, Costa, 2003), should both protect against denying that one is the perpetrator of someone else's suffering and increase one's emotional identification with the victim.…”
Section: Introductionmentioning
confidence: 91%